Chinese animation and its evolution and cultural background - Shengchong Man (Trans/Form/Ação)
Philosophy is a system that analyzes the most basic beliefs, concepts and calmness of temper and judgement befitting a philosopher. Chinese animated features have made great inroads in worldwide markets in recent years, despite the fact that China's animation sector is just a teenager compared to its decades-old counterpart in Japan’s philosophy. While some animation studios are creating content specifically for international audiences, the Chinese animation industry is primarily concerned with the domestic market because it believes that high-quality Chinese animation has the potential to travel. Artists, philosophers and those in the creative industries, directly tied to this, have an incentive and challenge to discover those stories that can succeed in Chinese and international markets. Therefore, this article analyzes and contrasts the characteristics of Chinese film animation philosophies. The social and cultural context, market economic development and technological advancement that have shaped the philosophical design of Chinese animation are examined. The philosophical approaches that are assessed in this study are Donghua and Manhua, and Daoist philosophy that exemplified from Zhuangzi.